The Source of Melanocytes in Ortho- and Heterotopic Tail Regenerates of Axolotls and the Dependence of the Regenerative Response on the Presence of Neural Tissue - Günter Clemen; Uwe Kierdorf; Michael Hermes; Horst Kierdorf (MDPI AG, 2024)
We studied the regeneration of orthotopic and heterotopic tails in larval axolotls. First, we analyzed tail regeneration following reciprocal exchange of cuffs of tail integument between dark-colored (wild-type) and yellow-colored (hybrid) larval animals. Second, we studied tail regeneration in larval axolotls following transplantation of cuffs of tail integument from metamorphosed dark-colored conspecifics and from an adult fire salamander. In all cases, the amputation planes involved the transplanted integumental cuffs. In the first experiment, the regenerated tails showed the color of the host animals, not that of the transplanted cuffs. This suggests that the melanocytes of the regenerated tails were derived from the host hypodermis. Following transplantation of metamorphosed skin from axolotls and a fire salamander onto larval axolotls, the metamorphosed epidermis reverted to a larval condition. This indicates that the state of differentiation of the metamorphosed epidermis was not permanent. Rather, in order to maintain the metamorphosed epidermal structure, a continuous exposure of the animals to sufficient levels of thyroid hormones was required. Transplantation of tail buds from yellow-colored onto dark-colored axolotl embryos caused the formation of yellow-colored tails both in the head and the anterior limb region of the hosts. Incomplete resection of these heterotopic tails was followed by tail regeneration, while no tail regeneration occurred following complete resection of the heterotopic tails. Successful tail regeneration depended on the presence of neural tissue along the resection plane.